2010
DOI: 10.1111/j.1447-0756.2010.01301.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal risk factors for small-for-gestational age newborns in Japanese dichorionic twins

Abstract: Cigarette smoking and weight gain control are relatively modifiable factors for which interventional management is necessary to avoid perinatal problems arising from SGA pregnancy. Further studies are needed to investigate optimal nutrition, health guidance and subsequent weight gain control that lead to concrete improvement in maternal and infant prognoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…developed a prediction model based on maternal race, education, marital status, parity, time of first perinatal care visit, cigarette abuse and paternal race. Inde et al 7 . identified correlations between DC twins and other maternal characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…developed a prediction model based on maternal race, education, marital status, parity, time of first perinatal care visit, cigarette abuse and paternal race. Inde et al 7 . identified correlations between DC twins and other maternal characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with AGA peers, growth‐restricted fetuses have a relatively smaller size, which allows for easier passage of these fetuses through the maternal parturient canal. Although they are likely to show chronic intrauterine hypoxia and low reserve faculties, 7 FGR/SGA is a favorable factor for SVD as the maternal perinatal outcome. However, because an intervention to one twin regardless of the AGA/SGA status affects its co‐twin regardless of the AGA/SGA status, some direct comparisons between AGA neonates and SGA peers cannot be performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the high-risk factors for twin IUGR have already been identified, such as low maternal weight gain and tobacco use [3][4][5], although most of the common risk factors in single pregnancies are not significant for twin IUGR [1]. It should be noted that twin pregnancies are far more complicated than single pregnancies, and twin pregnancies present some unique situations.…”
Section: Introductionmentioning
confidence: 94%
“…Over the past few decades, the incidence of twin pregnancies has increased by nearly 70% because of the widespread use of assisted reproductive technology [ 3 ], which means that DD twin pregnancies have also been increasing. Inde et al reported that 32.9% of patients who had DD twins received in vitro fertilization [ 4 ]. Accordingly, we reviewed our cases and the literature to investigate the management and timing of delivery in DD twins with sFGR and almost complete growth restriction.…”
Section: Introductionmentioning
confidence: 99%